Feasibility Study of Using the Integrated Telemedicine Platform "IS-cardio" for Outpatient Cardiological Rehabilitation: Single-Centered Cohort Study - Elena V. Kotelnikova; Vladimir I. Gridnev; Olga M. Posnenkova; Valeriy N. Senchikhin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. The implementation of remote cardiac rehabilitation (RCR) technology based on telemedicine platforms (TMP) requires a preliminary assessment of the feasibility of use. AIM. A preliminary study of the feasibility of using the integrated TMP "IS-cardio" to perform RCR in patients with cardiovascular diseases (CVD) in the context of need, feasibility and acceptability. MATERIALS AND METHODS. Single-center cohort study of patients (n = 33; 75 % men; mean age 56 ± 8 years) with CVD. Testing of the TMP «IS-cardio» was carried out during 12-week physical training (PT) programs with an intensity of 55 %. Feasibility was assessed according to the following criteria: need, feasibility, acceptability. Data on need and acceptability were obtained from a patient survey. Feasibility was assessed as the proportion of patients completing RCR. Remote monitoring was performed using heart rate, blood pressure, electrocardiogram and mobile application recorders. Feedback was provided in the form of electronic reports and delayed consultation. Patient satisfaction was assessed in points. RESULTS. 79.2 % of respondents were interested in telemedicine monitoring. 100 % of patients completed RCR; 12 patients (39.6 %) fully completed the PT program. The patients' activity amounted to 2.4 ± 0.7 PT sessions per week; the average duration of PT was 56.5 ± 29.8 min/week. With a total satisfaction of 29.0 ± 3 points, the level of RCR was highly rated (3.85 ± 0.16 points) as a real solution to the problem associated with the presence of CVD (3.67 ± 0.34 points). DISCUSSION. The medical-technological solution TMP "IS-cardio", combining the principles of traditional cardiac rehabilitation with telecardiology tools (monitoring based on digital recorders, automatic data transfer and feedback) met the criteria for the feasibility of using TMP with a similar concept. CONCLUSION. The high demand for remote monitoring, feasibility, and patient satisfaction of RCR may indicate the feasibility of its use for implementation of its programs.